Impact of balloon guide catheter versus conventional guide catheter on technical and clinical outcomes in mechanical thrombectomy for acute ischemic stroke: a systematic review and meta-analysis - Hunain Shahbaz; Aleena Amir Malik; Mariya Khan; Umar Kifayat; Aisha Allah Baksh; Kosar Ajmal; Muhammad Shah Jehan; Sarosh Awan; Sidra Amjad; Hadia Mohsin; Javeria Fayyaz; Muhammad Ishaq; et al. (Egyptian Journal of Neurosurgery, 2026)
Abstract Background Endovascular thrombectomy (EVT) is standard treatment for large vessel occlusion stroke, but the role of balloon guide catheters (BGCs) remains debated. This meta-analysis evaluates BGC versus standard catheters, pooling observational data with the only available randomised trial (PROTECT-MT). Methods Following PRISMA guidelines, observational studies and PROTECT-MT were retrieved from PubMed, Embase, and Cochrane until June 2026. Primary outcomes were excellent (mRS 0–1) and favourable (mRS 0–2) functional recovery at 90 days, 24-hour NIHSS, and procedure time. Secondary outcomes included symptomatic intracranial haemorrhage (sICH), first-pass recanalization (FPR), and 90-day mortality. Random-effects models were used. Post-hoc exploratory subgroup analyses by geographic region and study design investigated heterogeneity. Evidence certainty was assessed using GRADE. Results Five observational studies and one RCT (2,961 patients; 1,661 BGC, 1,300 non-BGC) were included. BGC use was associated with significantly higher excellent functional outcomes (RR 1.30, 95% CI 1.10–1.53; low certainty) but no difference in favourable outcomes (RR 1.02, 95% CI 0.84–1.24; very low certainty), and significantly higher odds of FPR (OR 2.48, 95% CI 1.76–3.48; moderate certainty). Neither sICH (RR 0.65, 95% CI 0.41–1.02) nor mortality (RR 0.76, 95% CI 0.53–1.08) reached significance overall (both very low certainty). By study design, observational studies alone showed a significant reduction in mortality (RR 0.66, 95% CI 0.46–0.94) and sICH (RR 0.54, 95% CI 0.39–0.74) with BGC, whereas PROTECT-MT alone showed a non-significant trend toward higher rates of both (mortality RR 1.51; sICH RR 1.34); this subgroup difference was significant for mortality ( P = 0.005) and sICH ( P = 0.006). Study design was also a significant effect modifier for favourable outcome (P for interaction = 0.001): retrospective studies showed benefit (RR 1.35) while prospective studies did not (RR 0.90). Region was not a significant modifier. Conclusions BGC use during EVT is associated with higher excellent functional recovery and first-pass recanalization. The mortality and sICH benefits suggested by observational data were not replicated in the only available randomised trial, with significant discordance between the two evidence streams. Given predominantly very-low-certainty evidence and this discordance, findings do not support a recommendation for or against routine BGC use pending confirmatory randomised evidence.